Dimensionamento de viga em concreto protendido para suporte de tombador de cargas - Daga, Rafaela Caroline (2022)
The use of prestressing stands out in industrial works due to the possibility of increasing the load capacity or as a factor to reduce the dimensions of structural parts. This study evaluates the use of prestressing in a beam that supports the loads generated by a grain dumper, through analysis of the influence of the cable layout, the comparison of the section of the piece in conventional reinforced concrete with prestressed concrete, quantitative and volumes of materials. Using a standard grain dumper design, 11 calculation models were evaluated, considering reinforced concrete and prestressed concrete, using the TQS software, based on NBR 6118 (ABNT, 2014). The two constructive methods were compared, having as variables the cable tracing, in a straight and parabolic way, the action of accidental loads on the beam, and the cross section of the prestressed concrete beam. The results showed that it is possible to reduce the height of the beam section by 36.4% when prestressed concrete is used. The rectilinear layout of prestressing cables at the center of gravity of the cross section showed better performance in the stress analysis, as the compressive force due to prestressing needs to be high to meet accidental loads, and the application of eccentricity to the cable would result in stresses of excessive tension on the upper face of the beam for combinations with permanent load only. Despite the reduction in the concrete volume of the prestressed beam, it is recommended to evaluate the economic viability of using this method for structures with high accidental load, taking into account the cost of materials and services for the application of prestressing.